VLSI and post-CMOS electronics. Volume 1 Design, modelling and simulation - Dhiman, Rohit; Chandel, Rajeevan (Materials, circuits and devices series ;, 2019)
VLSI and Post-CMOS Electronics is a useful reference guide for researchers, engineers and advanced students working in the area of design and modelling of VLSI and post-CMOS devices and their circuits